Clinical outcome and influencing factors of differentiated thyroid cancer patients with radioiodine-refractory lung metastasis - Wang, Congcong; Li, Yutian; Qin, Guohua; Li, Jiao; Wang, Guoqiang; Liu, Xinfeng; Wang, Xufu (Frontiers in Endocrinology, 2025)
PurposeA subset of patients with differentiated thyroid cancer and lung metastases (DTC-LM) may progress to radioiodine-refractory (RAIR) disease, which is associated with a poor prognosis. This study aimed to investigate the clinical outcomes and potential risk factors associated with RAIR disease in DTC-LM patients.Methods177 DTC-LM patients who underwent radioiodine (RAI) therapy at our center were retrospectively analyzed. Clinicopathological profiles were compared between the RAI-avid (RAIA) and RAIR groups. Univariate and multivariate regression analyses were conducted to identify risk factors for RAIR status and progressive disease (PD).ResultsOverall, 80 patients were included in the RAIR group, accounting for 45.2% of the total patients. Multivariate analysis revealed that older age and higher T stage were independent risk factors for RAIR disease. Age≥55 years (HR: 2.975, 95% CI: 1.424 -6.218, P = 0.004), RAI-avid status (HR: 4.315, 95% CI: 1.753 - 10.622, P = 0.001) and the ps-Tg≥528.5ng/mL (HR: 3.665, 95% CI: 1.656 - 8.107, P = 0.001)were identified as independent predictors of PD. Kaplan–Meier analysis revealed a lower progression-free survival (PFS) rate in the RAIR group than in the RAIA group (P< 0.001).ConclusionRAIR disease is common among DTC-LM patients and is associated with adverse clinical outcomes. Age, RAI avidity status, and ps-Tg levels serve as important predictors of PD. Early risk stratification and individualized management strategies are crucial to improving outcomes in DTC-LM patients.